Wrong papers in mathematics I. Paper by Cakoni F., Colton D., Monk P. in "Inverse Problems" and subsequent papers - Krutitskii, Pavel (International Journal of Applied Mathematical Research, 2012)
The long series of mistaken papers published in the mathematical journals with very high impact factor during 11 years is discussed. The following journals published these mistaken papers: Inverse Problems (1), Nonlinear Analysis (1), Boundary Value Problems (1), Journal of Differential Equations (1), Journal of Mathematical Physiscs (2), Mathematical Methods in the Applied Sciences (2). The number in brackets shows the number of published wrong papers involved in the discussion. This series of wrong papers has been generated by a mistake in the paper: Cakoni F., Colton D. and Monk P. The direct and inverse scattering problems for partially coated obstacles. Inverse Problems, 2001, v. 17, pp. 1997-2015.